2000
DOI: 10.1073/pnas.240269897
|View full text |Cite
|
Sign up to set email alerts
|

γ-Aminobutyric acid, acting through γ-aminobutyric acid type A receptors, inhibits the biosynthesis of neurosteroids in the frog hypothalamus

Abstract: Most of the actions of neurosteroids on the central nervous system are mediated through allosteric modulation of the ␥-aminobutyric acid type A (GABA A) receptor, but a direct effect of GABA on the regulation of neurosteroid biosynthesis has never been investigated. In the present report, we have attempted to determine whether 3␤-hydroxysteroid dehydrogenase (3␤-HSD)-containing neurons, which secrete neurosteroids in the frog hypothalamus, also express the GABAA receptor, and we have investigated the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 29 publications
(38 reference statements)
3
35
0
Order By: Relevance
“…However, no significant differences between suicide victims and nonpsychiatric controls for GABA A and GABA B receptor binding sites, [142][143][144][145] GAD activity, 141 and GABA concentration 146 have been found in several brain areas. Recently, support for abnormally decreased GABAergic neurotransmission in anterior cingulate, prefrontal cortex, and hippocampus in bipolar, but not unipolar disorder patients has been reported by several postmortem studies, as shown by decreased expression of GAD 65 and GAD 67 and decreased density of GABAergic neurons. [147][148][149][150] These post-mortem studies together sustain the hypothesis of low GABA brain activity in mood disorder patients, but not in suicide victims.…”
Section: 103mentioning
confidence: 82%
See 1 more Smart Citation
“…However, no significant differences between suicide victims and nonpsychiatric controls for GABA A and GABA B receptor binding sites, [142][143][144][145] GAD activity, 141 and GABA concentration 146 have been found in several brain areas. Recently, support for abnormally decreased GABAergic neurotransmission in anterior cingulate, prefrontal cortex, and hippocampus in bipolar, but not unipolar disorder patients has been reported by several postmortem studies, as shown by decreased expression of GAD 65 and GAD 67 and decreased density of GABAergic neurons. [147][148][149][150] These post-mortem studies together sustain the hypothesis of low GABA brain activity in mood disorder patients, but not in suicide victims.…”
Section: 103mentioning
confidence: 82%
“…In turn, pregnenolone can be metabolized to pregnanes (pregnenolone sulfate, pregnanolone, allopregnanolone) and androstanes (dehydroepiandrosterone, dehydroepiandrosterone-sulfate, dihydrotestoterone metabolites). 66 Although the mechanisms involved in the regulation of neurosteroids within the cells are still largely unknown, Do-Rego et al 67 have recently reported that GABA itself, acting through GABA A receptors, inhibits the activity of neurosteroidogenic enzymes. The effects of neurosteroids on GABA A receptors have been extensively investigated.…”
Section: Gabaergic Modulation Of Neuronal Activitymentioning
confidence: 99%
“…This could be consistent with the work from Girdler et al (2012) showing decreased conversion of progesterone to allopregnanolone in women with a history of depression. Research in a frog model also shows that GABA A receptor activation can lead to a downregulation of neuroactive steroid production, suggesting a potential negative feedback loop; however, this has not been investigated in humans (Do-Rego et al, 2000). Thus, while neurosteroidogenic pathways are well defined, the overall regulation of neuroactive steroids is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these different variables are also likely to be dependent upon one another. Finally, it is noted that activation of hypothalamic GABA A receptors has been shown to inhibit the activity of the steroidogenic enzymes, 3β-hydroxysteroid dehydrogenase and P450 C17 (17α-hydroxylase) and neurosteroid production in the hypothalamus, suggesting that neurosteroid potentiation of hypothalamic GABAergic transmission may be self-limiting (Do-Rego et al, 2000). A) Representative micrograph of an acutely isolated slice from a female mouse at the level of the mPOA and a patch electrode.…”
Section: Future Directionsmentioning
confidence: 99%